DEVELOPMENT, VALIDATION AND USE OF PRINCIPALS’ LEADERSHIP BEHAVIOURS MEASURING INSTRUMENT FOR SECONDARY SCHOOLS IN SOUTH EAST NIGERIA - Umeokwe, Eucharia Chikwuo (African Journal of Behavioural and Scale Development Research, 2022)
The work developed, validated, and used the instrument for measuring principals’ leadership behaviours in South East Nigeria. Instrumentation research design was used for the study. The work used 474 head principals and secondary schools from 14 education zones in the 5 states of South East selected through proportionate stratified random sampling technique. Guided by two research questions and one hypothesis. The instrument used for the study was design was Principals’ Leadership Behaviours Measuring Instrument (PLBMI). The PLBMI is a 102-item instrument that emerged after face validation by Measurement and Evaluation and Educational Management and Planning experts, from Michaeal University of Agriculture, Umudike. The face validated items were trial tested and the responses were subjected to factor analysis to determine the construct validity in research question one. The instrument reliability was established by method of internal consistency using Cronbach Alpha having index of 0.897. Data were analyzed using Normal Varimax Rotation method of factorial analysis. Mean ratings and S. D. were used in answering research question 2. While t-test was used in testing the null hypothesis. It was found out that fifty (50) items out of the One hundred and two (102) items met the requirements for acceptance as valid items and included in the instrument, while fifty two (52) items that were factorially invalid were discarded. The findings also showed effective mean at all the clusters of PLBMI, and no significant difference in the mean scores of the principals based on gender. Among the recommendations was that since the instrument is proved valid, it should be adopted by Post Primary Schools Management Board and Ministries of Education in the assessment of principals before assigning them to lead schools. This will avert the influence of subjectivity in the selection of principals.